The Italian information system on disability (Italian Journal of Public Health, 2008)
Background: The Disability Information System Project started in 2000 following an agreement between thecurrent Ministry of Social Solidarity and Istat in implementation of article 41-bis of Law 162/98, thathighlighted the need to promote statistical and cognitive surveys on disability.Methods: The System was created to meet the increasing attention of policy makers and society in general topeople with disabilities and their participation in society. The system provides statistical information ondisability by integrating and coordinating data sources available relating to this issue in Italy and to establishnew sources that are suitable for addressing the current information gaps.Discussion: Activities of Istat in recent years have reached the ambitious goal of transforming the extensivedata and numerous documents of an administrative nature on disability into statistical information. It meansto create an organised body of information, documented and processed using statistical tools that can beunderstood and used by policy-makers, experts, and citizens.Conclusions: The phenomena analysed are very often characterised by various dimensions that are unlikelyto be independent of one another. It is precisely in studying these phenomena that the information systemprovides significant added value since it makes it possible to have quicker and a guided access to themultiplicity of data sources that describe different aspects of a topic. This makes possible for the user tointegrate information and to create an overall or sufficiently comprehensive picture.
Keywords: information system; disability; social integration; indicators; data sources